2009
DOI: 10.1111/j.1439-0531.2008.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ductus Epididymis of the Alpaca: Immunohistochemical and Lectin Histochemical Study

Abstract: Our objective was to characterize epithelial cells lining the epididymal duct (caput, corpus, cauda) of the alpaca using AE1/AE3 cytokeratin antibodies and a battery of different lectins: Con-A, UEA-I, LTA WGA, GSA-II, GSA-IB4, SBA, PNA, ECA, DBA, MAL-II and SNA. Sialidase digestion and deglycosylation pre-treatments were also employed. The principal cells (PCs) along the epididymis showed differences in immunostaining patterns toward keratin antibodies. Lectin histochemistry demonstrated variations in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…These cells were reported in the initial epididymal segments in men (Fraile et al, 1996) and in other mammalian species (Martìnez-Garcìa et al, 1995). In the alpaca, they were observed to contain lectins and were postulated to regulate epididymal ionic composition and intraluminal pH (Parillo et al, 2009b).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These cells were reported in the initial epididymal segments in men (Fraile et al, 1996) and in other mammalian species (Martìnez-Garcìa et al, 1995). In the alpaca, they were observed to contain lectins and were postulated to regulate epididymal ionic composition and intraluminal pH (Parillo et al, 2009b).…”
Section: Resultsmentioning
confidence: 96%
“…There are several studies describing male genital tract of alpacas. In particular, Parillo et al (2009aParillo et al ( , 2009bParillo et al ( , 2012 reported a detailed distribution of glycosidic residues of glycoconjugates in the epidydimis, testis and spermatozoa. Wang et al (2011) reported that NGF is espressed in the testis of alpaca .…”
Section: Innervation and Immunohistochemical Characteristics Of Epidimentioning
confidence: 99%
“…Therefore, they have been widely used in histochemical analysis for the detection of sugar chains and the characterization of cell populations in the epididymis in species including humans (Arenas et al, 1996(Arenas et al, , 1998 (Calvo et al, 1995), horses (Parillo et al, 1997), boars (Calvo et al, 2000), dogs (Schick et al, 2009), and alpacas (Parillo et al, 2009). It has been shown that various sugar chains are abundant in the epithelial cells of the developing mouse epididymis (Bendahmane and Abou-Haila, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…2F). The apical mitochondria-rich cells (AMRCs), that we previously described in the alpaca epididymis [10], expressed nNOS in the caput ( Fig. 2A) and corpus (Fig.…”
Section: Resultsmentioning
confidence: 99%